Synthesis and characterization of three sandwich complexes of zirconium with disubstituted indenyl ligands - Kundu, Kalipada; Reb, Alexander (Journal of the Bangladesh Chemical Society, 2012)
The preparation of three sandwich complexes of zirconium (1,2,3) with disubstituted indenyl ligands and their characterization using 1H, 13C and 29Si-NMR and mass spectroscopy is described. DOI: http://dx.doi.org/10.3329/jbcs.v24i2.9710 Journal of Bangladesh Chemical Society, Vol. 24(2), 209-214, 2011